Simulation of localized surface plasmon resonance activities on gold nanoparticles - Li, Fengshi. (2012)
Strong electromagnetic enhancements can be provided by noble metal nanostructures via the excitation of localized surface plasmons using light. This has aroused great interest in the field of utilizing the unique optical properties of metal nanoparticles, especially gold or silver, for SERS applications.